Public Service Innovation Using Smart Governance - Ryu , Seung; Kim, Hyun; Hong, Soon (Journal of Public Policy and Administration, 2022)
Purpose: This study determines the possibility of public service innovation to meet the rapid changes in information technology (IT) and the need for new governance by analyzing three cases in South Korea. Methodology: The Smart Governance-Decision Support Systems (SG-DSS) in this study is a new form that guarantees the voluntary participation of citizens by applying IT to governance. SG-DSS supports the demand response that fulfills universal values and decisions about priorities by collecting citizens' needs. It also encourages citizens or stakeholders to participate in establishing implementation plans that are more specific and fit for reality, giving legitimacy to public service policies and developing them into a driving force. Findings: The three case studies on Korean public policies show how public opinions reflect public service policies. Therefore, the findings of this study could lay the foundation for customized public services based on intelligent citizen participation by overcoming the current limitations. Unique contribution to theory, practice and policy: SG-DSS supports the demand response that fulfills universal values and decisions about priorities by collecting citizens' needs. It also encourages citizens or stakeholders to participate in establishing implementation plans that are more specific and fit for reality, giving legitimacy to public service policies and developing them into a driving force. The core value of smart governance is to apply IT innovations such as big data and AI to public services. Furthermore, advanced technology enables the collection and application of actual public opinions, thereby improving public to be more objective and efficient.